Proposition méthodologique en ergotoxicologie pour révéler les expositions à des produits chimiques - Louis Galey; Nathalie Judon; Caroline Jolly; Fabienne Goutille; Sarah Morelot; Marion Albert; Olivier Lhospital; Patrick Martin; Catherine Noel-Suberville; Pierrick Pasquereau; Agnès Aublet-Cuvelier; Brahim Mohammed-Brahim; et al. (Activités)
Over the last fifteen years ergotoxicology has been using an interdisciplinary approach to develop models and methods (Mohammed-Brahim & Garrigou, 2009; Garrigou, 2011) in an effort to preserve occupational health. This approach is based on toxicological knowledge and on methods of work activity analysis. The purpose of this article is to present a method based on the use of real time measurements, synchronized with video recordings of work situations. This stems from methodological development in ergotoxicology. The methodology calls for use of the video exposure monitoring (VEM) technique to detect situations of exposure and to formulate an in-depth work activity analysis. The objective of this method is to uncover situations where there is chemical exposure and to help companies recognize this. Three case studies are presented in this article. In the conclusion, we discuss the perspectives of this methodology for ergonomics with a view to to developing prevention practices involving workers, their management and occupational health enablers.